2018
DOI: 10.1007/s00198-018-4427-7
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet, diet quality, and bone mineral content in adolescents: the HELENA study

Abstract: An overall dietary score or index is not associated with BMC in our adolescent Spanish sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Various studies investigated the effect of Mediterranean diet on bone health and reported a positive association [ 50 , 51 , 52 ] or no association [ 53 , 54 ]. A traditional Mediterranean diet is characterized by low intake of meat and meat products, moderate intake of dairy products, and high amounts of fruits and vegetables (rich in antioxidants and polyphenols), fish, and cereals in unprocessed form [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies investigated the effect of Mediterranean diet on bone health and reported a positive association [ 50 , 51 , 52 ] or no association [ 53 , 54 ]. A traditional Mediterranean diet is characterized by low intake of meat and meat products, moderate intake of dairy products, and high amounts of fruits and vegetables (rich in antioxidants and polyphenols), fish, and cereals in unprocessed form [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HELENA study failed to show, in Spanish adolescents, the association between Mediterranean diet and BMC ( 59 ) as well as a study of Monjardino et al ( 60 ), which found no association between forearm BMD and different dietary patterns. The work of Shin et al observed that adolescents in the highest tertile with a dietary pattern rich in cereal and milk score significantly a reduced chance of having low BMD than do those in the lowest tertile ( 61 ).…”
Section: Dietary Compositionmentioning
confidence: 91%
“…We observed no association between MDP and bone-related markers in our population of overweight and obese children, which concur with previous studies. Julian et al [ 29 ] and Monjardino et al [ 48 ] observed no association of the MDP assessed by means of two 24-hour recall and the KIDMED with and BMC and aBMD in adolescents. Of note is that in the Monjardino et al [ 48 ] study, they excluded those items from the KIDMED that had no relation with the Mediterranean diet, as we did it in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it also provides molecules with anti-inflammatory properties and bioactive molecules with antioxidant effects, which contribute to bone development [ 25 , 26 ]. The MPD has shown great benefits in the treatment and prevention of multiple noncommunicable diseases such as obesity and diabetes [ 27 , 28 , 29 , 30 , 31 , 32 ], but only a few studies have examined its association with bone health in young population [ 28 , 29 ], obtaining nonsignificant findings. By contrast, a positive effect of the adherence to the Mediterranean dietary pattern on BMD has been observed in adult population [ 30 ].…”
Section: Introductionmentioning
confidence: 99%